The prevalence and clinical characteristics of cystic fibrosis in South Asian Canadian immigrants. Issue 7 (21st June 2005) - Mei-Zahav, M; Durie, P; Zielenski, J; Solomon, M; Tullis, E; Tsui, L-C; Corey, M
Abstract : Background: Cystic fibrosis (CF) is considered to be rare among individuals from the Indian subcontinent. Furthermore, affected individuals are reported to experience a more severe clinical course. Aims: It was hypothesised that CF is under diagnosed in people of South Asian origin and therefore the prevalence may be higher than previously estimated. Methods: The prevalence of CF in the South Asian and in the general population living in the same geographic region (Metropolitan Toronto) were compared between 1996 and 2001. Population data were obtained from the Canadian census survey. CF phenotype and genotype data were obtained from the Toronto CF database. Results: Among 381 patients with CF, 15 were of South Asian descent. The age related prevalence of CF among the South Asian and general populations was: 0–14 years, 1:9200 versus 1:6600; 15–24 years, 1:13 200 versus 1:7600; older than 25 years, 1:56 600 versus 1:12 400. Age at diagnosis, duration and severity of symptoms at diagnosis, current nutritional status, and FEV1 were similar in the two groups. While not significant, FEV1 tended to be lower (48% versus 57% predicted) among adult South Asians, compared to the general CF population. Also, the percentage with pancreatic sufficiency was higher (27% versus 16%) and the frequency of ΔF508 allele was lower (50% versus 65.1%). Conclusions: These data suggest that the prevalence and natural history of CF in South Asians is similar to that among individuals of European origin. The relatively lower prevalence among older South Asians may reflect an improving recognition of CF in this ethnic subgroup.